Thiazolidinedione-8 Alters Symbiotic Relationship in C. albicans-S. mutans Dual Species Biofilm - Feldman, Mark; Ginsburg, Isaac; Al-Quntar, Abed; Steinberg, Doron (Frontiers in Microbiology, 2016)
The small molecule, thiazolidinedione-8 (S-8) was shown to impair biofilm formation of various microbial pathogens, including the fungus Candida albicans and Streptococcus mutans. Previously, we have evaluated the specific molecular mode of S-8 action against C. albicans biofilm-associated pathogenicity. In this study we investigated the influence of S-8 on dual species, C. albicans-S. mutans biofilm. We show that in the presence of S-8 a reduction of the co-species biofilm formation occurred with a major effect on C. albicans. Biofilm biomass and exopolysaccharide (EPS) production were significantly reduced by S-8. Moreover, the agent caused oxidative stress associated with a strong induction of reactive oxygen species (ROS) and hydrogen peroxide uptake inhibition by a mixed biofilm. In addition, S-8 altered symbiotic relationship between these species by a complex mechanism. Streptococcal genes associated with quorum sensing (comDE and luxS), EPS production (gtfBCD and gbpB), as well as genes related to protection against oxidative stress (nox and sodA) were markedly upregulated by S-8. In contrast, fungal genes related to hyphae formation (hwp1), adhesion (als3), hydrophobicity (csh1) and oxidative stress response (sod1, sod2 and cat1) were downregulated in the presence of S-8. In addition, ywp1 gene associated with yeast form of C. albicans was induced by S-8, which is correlated with appearance of mostly yeast cells in S-8 treated dual species biofilms. We concluded that S-8 disturbs symbiotic balance between C. albicans and S. mutans in dual species biofilm.